HUBUNGAN JUMLAH KONSUMSI BATANG ROKOK TERHADAP NILAI ARUS PUNCAK EKSPIRASI PADA LAKI-LAKI DEWASA MUDA - Ni Putu Suci Sukreni; Ari Wibawa; I Made Krisna Dinata (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2017)
ABSTRACTSmoking can affect health, especially lung health. This study aims to find the relationship of total cigarette consumptionand peak expiratory flow rate values. Using cross-sectional analytical design conducted in 2017 in March on UdayanaUniversity Faculty of Engineering students aged 20-24 years with sampling method consecutive sampling obtained91 respondents. Measurement of the Total Cigarette Smoking Quantity was done using a questionnaire thatrefers to the smoking habit and Peak Flow Meter to assess the Peak Flow of Expiration. Data was analyzed bySpearman's Rho correlation coefficient test showed that p = 0,038 (p <0,05) with r = -0,218. In conclusion there is asignificant relationship but the strength is weak and negative or not unidirectional between total cigarette consumptionand peak expiratory flow rate on young adult men. The total of cigarettes consumption per day amounted to 10.69stems. While the average peak expiratory flow rate value amounted to 405.16 L / min.Keywords : Total Cigarette Consumption, Peak Expiratory Flow Rate Values, Young Adult Men